2017
DOI: 10.1089/fpd.2016.2273
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Medium Chain Fatty Acid Feed Supplementation for ReducingSalmonellaTyphimurium Colonization in Turkey Poults

Abstract: Studies indicate that persistent Salmonella colonization occurs in poultry that are infected early in life, leading to both food safety and public health concerns. Development of improved preharvest Salmonella management strategies is needed to reduce poultry product contamination. The objective of this study was to evaluate the efficacy of a product containing medium chain fatty acids (MCFA) for reducing early Salmonella colonization in turkey poults. Day-of-hatch turkeys were provided a standard starter diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…A study conducted by Evans et al [ 157 ] revealed that when medium-chain fatty acids were supplemented through feed, a 1 log 10 reduction in the cecal colonization of S. Typhimurium was observed in turkey poults 3 days after inoculation. Also, supplementation of caprylic acid at 0.7% and 1.0% significantly reduced Salmonella after 5 days of challenge in chickens [ 158 , 159 ].…”
Section: Antibiotic Alternatives Against Salmonellamentioning
confidence: 99%
“…A study conducted by Evans et al [ 157 ] revealed that when medium-chain fatty acids were supplemented through feed, a 1 log 10 reduction in the cecal colonization of S. Typhimurium was observed in turkey poults 3 days after inoculation. Also, supplementation of caprylic acid at 0.7% and 1.0% significantly reduced Salmonella after 5 days of challenge in chickens [ 158 , 159 ].…”
Section: Antibiotic Alternatives Against Salmonellamentioning
confidence: 99%
“…Electron donors that are suitable for chain elongation processes, such as ethanol (Steinbusch et al, 2011 ), hydrogen (Steinbusch et al, 2011 ), methanol (Chen et al, 2016b ), and lactic acid (Zhu et al, 2015 ), can also be produced from organic residues (e.g., lignocellulosic bioethanol). Particularly, MCFAs can be used for production of aviation fuels (Harvey and Meylemans, 2014 ; Khor et al, 2017 ) and for other end-products such as solvents, lubricants, feed additives for poultry (Evans et al, 2017 ) and piglets (Hanczakowska et al, 2013 ), plastics and dyes (Angenent et al, 2016 ). The main advantage of chain elongation is that it is catalyzed by an anaerobic open-culture reactor microbiome (i.e., sludge).…”
Section: Introductionmentioning
confidence: 99%
“…Speciality chemicals such as n-caproate and iso-butyrate are valuable products of the carboxylate platform, with a broad range of potential applications in agriculture and industry [1][2][3]. For example, n-caproate can be used as promoter of plant growth and feed additive, or as precursor for the production of biofuels, lubricants and fragrances [1,[4][5][6][7]. Currently, n-caproate is mainly produced from vegetable oils such as palm kernel oil [8], though it can be produced from more sustainable feedstocks such as agro-industrial waste by anaerobic fermentation and microbial chain elongation [9,10].…”
Section: Introductionmentioning
confidence: 99%